Utilizing Plastic Waste into Creative Economic Products through a Community-Based Recycling Approach - Insira Insani Fitri; Tomi Apra Santosa; Faras Puji Azizah; Fantoni; Yucke Desma Kartika; Ilwandri (LPPM Akademi Teknik Adikarya, 2025)
The problem of plastic waste is an increasingly complex environmental issue due to the increasing consumption of single-use plastics and the low level of community-based management. This study aims to analyze the use of plastic waste as a creative economy product through a community-based recycling approach, a sustainable solution that integrates environmental, social, and economic aspects. This approach positions the community as the primary actor in the waste management process, from sorting and processing to the creation of economically valuable products, thereby encouraging active participation and increasing environmental awareness. The research method used was a qualitative approach with a case study design, involving field observations, in-depth interviews with community actors, and analysis of documentation related to community-based recycling activities. The results show that utilizing plastic waste through the creative economy not only reduces the volume of plastic waste but also has a positive impact on increasing community income, strengthening social capacity, and fostering local economic independence. The resulting products possess aesthetic and functional value that is competitive in the local market. The study's conclusions confirm that the community-based recycling approach is an effective and sustainable strategy for managing plastic waste while simultaneously encouraging the development of the community's creative economy. Therefore, policy support, ongoing mentoring, and collaboration between the government, academia, and the private sector are needed to expand the implementation of this model as part of environmentally conscious development and community empowerment.